Medical survey of female boxing in Italy in 2002-2003 - Bianco, M; Pannozzo, A.; Fabbricatore, C.; Sanna, N.; Moscetti, M.; Palmieri, V.; Zeppilli, P. (British Journal of Sports Medicine, 2005)
Background: Female boxing has been permitted in Italy since 2001. According to the latest Italian laws, athletes applying to become boxers have to pass a pre-participation medical examination.